Haemostasis treatment using dual red imaging during endoscopic submucosal dissection: a multicentre, open-label, randomised controlled trial. Issue 1 (30th March 2019) - Fujimoto, Ai; Saito, Yutaka; Abe, Seiirhicro; Hoteya, Shu; Nomura, Kosuke; Yasuda, Hiroshi; Matsuo, Yasumasa; Uraoka, Toshio; Kuribayashi, Shiko; Saito, Itaru; Tsuji, Yosuke; Maehata, Tadateru; et al.
Abstract : Introduction: Patients scheduled to undergo oesophageal, gastric and colorectal endoscopic submucosal dissection (ESD) are to be investigated to verify the efficacy of dual red imaging (DRI) for establishing haemostasis during ESD. Methods and analysis: The trial is designed as a multicentre, open-label randomised, parallel-group, controlled intervention study. Registered patients will be randomly assigned to DRI and white light imaging (WLI) groups. In the DRI group, the mucosal incision and submucosal dissection will be performed by WLI, and haemostasis will be managed by DRI when bleeding occurs. In the WLI group, the mucosal incision and submucosal dissection are to be performed by WLI and the haemostasis management is to be performed by WLI. The primary endpoint is the time from the recognition of bleeding up to the achievement of complete haemostasis (haemostasis time). The secondary endpoints are the operation time, the proportion of cases in which perforation occurs, and the psychological stress experienced by the endoscopist during haemostasis treatment. Ethics and dissemination: This trial was approved by the Keio University Review Board for Clinical Trials (5 December 2016). Discussion: This will be the first multicentre collaborative research using DRI for haemostasis treatment during ESD. When the safety and simplicity of DRI as a treatment for haemostasis during ESD can be proven, the ESD procedure can be simplified and disseminated more widely in clinical practice. Trial registration number: UMIN000025134